Double Facial Nerve Trunk Emerged from the Stylomastoid Foramen and Petrotympanic Fissure: A Case Report - Kilic, Cenk (The Korean Academy of Medical Sciences, 2010)
There are several studies concerning branches of the facial nerve, but we encountered less information about the trunk of the facial nerve in the literature. During the routine dissection of a 65-yr-old Caucasian male cadaver, double facial nerve trunk emerged from the stylomastoid foramen and petrotympanic fissure were encountered. Because of an extremely rare variation, we presented this case report. In addition this cadaver had two buccal plexuses. These plexuses and other branches were formed to structures like to polygon. These anatomic peculiarities were described, photographed and illustrated. Finally, magnetic resonance imaging was performed by using 1.5T scanner to this cadaver. The facial nerve trunk can be damaged during surgical procedures of the parotid gland tumours and submandibular region. Surgeons who are willing to operate on this area should be aware of the possible anatomical variations of the facial nerve trunk.